2008
DOI: 10.1242/dev.023663
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous and non-autonomous Shh signalling mediate the in vivo growth and guidance of mouse retinal ganglion cell axons

Abstract: In non-mammalian vertebrates, the relatively homogeneous population of retinal ganglion cells (RGCs) differentiates and projects entirely to the contralateral side of the brain under the influence of sonic hedgehog (Shh). In mammals, by contrast, there are two different RGC types: the Zic2-positive ipsilateral projecting and the Isl2-positive contralateral projecting. We asked whether the axons of these two populations respond to Shh and if their response differs. We have also analysed whether midline-and RGCd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
100
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 72 publications
4
100
1
Order By: Relevance
“…However, as Shh activity is important to pattern the midbrain regions surrounding the ventral hypothalamus (just adjacent to the optic chiasm) during retinal axon development (Dale et al, 1997;Barresi et al, 2005;Manning et al, 2006), it is likely that blocking Shh signaling for 5 d in developing embryos can cause patterning defects. Thus, as noted by the authors (Sánchez-Camacho and Bovolenta, 2008), it is possible that the effects observed are not due to a direct guidance effect of Shh but rather to changes in expression of other guidance cues. In a second set of experiments, an inhibitor of the Shh signaling mediator Smo was electroporated in the developing mouse visual system at E13.5 and analyzed at E16.5 (Sánchez-Camacho and Bovolenta, 2008).…”
Section: The Roles Of Shh In the Guidance Of Rgc Axonsmentioning
confidence: 77%
See 4 more Smart Citations
“…However, as Shh activity is important to pattern the midbrain regions surrounding the ventral hypothalamus (just adjacent to the optic chiasm) during retinal axon development (Dale et al, 1997;Barresi et al, 2005;Manning et al, 2006), it is likely that blocking Shh signaling for 5 d in developing embryos can cause patterning defects. Thus, as noted by the authors (Sánchez-Camacho and Bovolenta, 2008), it is possible that the effects observed are not due to a direct guidance effect of Shh but rather to changes in expression of other guidance cues. In a second set of experiments, an inhibitor of the Shh signaling mediator Smo was electroporated in the developing mouse visual system at E13.5 and analyzed at E16.5 (Sánchez-Camacho and Bovolenta, 2008).…”
Section: The Roles Of Shh In the Guidance Of Rgc Axonsmentioning
confidence: 77%
“…Retinal explants isolated from Boc ϩ/Ϫ and Boc Ϫ/Ϫ E15.5 embryos were cultured for 24 h. RGC axon dynamics were analyzed by time-lapse microscopy after addition of 10 nM ShhN. (Trousse et al, 2001;Kolpak et al, 2005;Sánchez-Camacho and Bovolenta, 2008) and it is present in the chiasmatic zone (Torres et al, 1996;Marcus et al, 1999;Wallace and Raff, 1999;Trousse et al, 2001). Based on these data and on our finding that Boc is expressed in ipsilateral RGCs, we hypothesized that Boc might function as a Shh receptor which prevents these axons from crossing the optic chiasm.…”
Section: Ipsilateral Rgcs Express the Shh Receptor Bocmentioning
confidence: 99%
See 3 more Smart Citations